Assessment of the Dental Condition of Patients with Impaired Cerebral Circulation - Muratova Saodat Kadirovna; Shukurova Nodira Tillayevna (Genius Journals, 2023)
In our studies, the relationship between pathogenetic and functional disorders of cerebral ischemia and the functional state of the oral mucosa was revealed. The use of a comprehensive diagnostic and preventive approach was justified, taking into account the presence of cerebral circulation disorders in the disease of the SOPR in the practice of a dentist. Pathogenetic justified sequence of application of preventive methods that make up the complex - dynamic monitoring of patients in order to determine the effectiveness of the treatment used and the need for repetition of the course of treatment.
Keywords: oral mucosa; periodontal disease; chronic cerebral ischemia